Answer:
-4x + 12
Step-by-step explanation:
2(x+6)-6x
2x + 12 - 6x
combine llike terms
2x - 6x = -4x
-4x + 12
Answer:
C) 20, 4
Step-by-step explanation:
X = 5y
2x + 5y = 60
substitute in 5y for x: 2(5y) + 5y = 60
10y + 5y = 60
15y = 60
y = 4
x = 5y
x = 5(4) = 20
True
plz thank me, it motivates me to answer more of your questions :)
Answer:
D. 50
Step-by-step explanation:
a = 90° (angle subtended in semicircle)
a + c + 40° = 180° (by angle sum postulate of a triangle)
90° + c + 40° = 180°
c + 130° = 180°
c = 180° - 130°
c = 50°